Exploring correlates for paid versus unpaid internships or co-ops for graduating business students. Issue 6 (17th August 2020) - Blau, Gary; Lopez, Andrea B.
Abstract: Using a complete data sample of 579 graduating business seniors, this study successfully created separate items for measuring paid internships/cooperative education (co-ops) and unpaid internships/co-ops. Students reported lower frequencies for self-reported paid and especially unpaid internships/co-ops. Several correlates were found to be differentially related to these types of internships, including securing full-time employment by graduation being more positively related to having paid internships/co-ops, while being self-employed by graduation being more positively related to having unpaid internships/co-ops. Completing a professional development course earlier in one's college program was found to be positively related to both types of internships/co-ops. Study limitations and future research issues are discussed.